Pedagogical Support for Young Children Affected by Emergency Situations: Principles and Mechanisms - Nehrii, Olha (Educological discourse, 2026)
The article examines the principles and mechanisms of pedagogical support for young children affected by emergencies, including the full-scale war in Ukraine. The emphasis is placed on the importance of timely pedagogical assistance as a factor in stabilising the emotional state of young children and restoring their basic sense of safety. The study identifies key principles of pedagogical support for young children affected by emergencies: an individualised approach, unconditional support, partnership-based interaction with the family, as well as consistency and intentionality of pedagogical influence. The presented principles of pedagogical support for young children affected by emergencies were developed and piloted within the international project «Emergency Early Childhood Development Support for Ukrainian Refugees» (ECDUR), initiated and implemented by UNICEF in partnership with the European Association of Service Providers for Persons with Disabilities (EASPD) from December 2022 to December 2023, with national coordinators Imago Foundation (Poland) and FONSS (Romania). The article proposes key mechanisms for implementing pedagogical support for young children affected by emergencies both in early childhood education settings and at home (by parents or caregivers). The author also provides a definition of «pedagogical support for a young child affected by an emergency» as a purposeful process of creating a safe, supportive, and developmentally enriching environment that promotes emotional stabilisation, the formation of trust in the world, and the harmonious development of the child. The practical significance of the study lies in the potential application of its results to the work of early childhood educators, psychologists, social workers, and parents or caregivers, enabling the development of an effective system of support for young children in emergency situations.